Pengaruh Kompensasi Dan Disiplin Terhadap Prestasi Kerja Karyawan Pt. Izone Indonusa C&F Perfumery - C dan Arni Kurniati (Fakultas Ekonomi Universitas Borobudur, 2017)
This study aimed to determine the effect of compensation and working discipline in the travel of PT. Izone Indonusa C & F Perfumery outlet Kelapa Gading to improve achievement by the employees using multiple linear regression analysis. The results of this study, in general there is influence between compensation and working discipline on employee performance. From the regression equation it can be explained that each regression coefficient is positive (1.279 and 0.80) that showed the effect proportional between compensation and working discipline on work performance; where every increase of the score variable compensation causing an increase in work performance of 1.279 and an increase of work discipline variable scores improve work performance amounted to 0.80. Thus the dominant factor in this case is formed work performance in the work environment is the Discipline of the employee. Discipline will determine employee performance PT. Izone Indonusa C & F Perfumery. Key words: compensation working, discipline dan performance.